Marketing Strategy for Agrotourism Development in Lampung Province Indonesia - Roslina Roslina; Rita Nurmalina; Mukhamad Najib; Yudha Heryawan Asnawi (Shirkah: Journal of Economics and Business, 2022)
The enormous potential for the development of agrotourism in Indonesia has not been explored efficiently due to nonoptimal marketing. Therefore, this research formulated the marketing strategy for the agrotourism sector in Lampung Province Indonesia. Purposive sampling was used to select the respondents based on the criteria of experts with experience, knowledge, or authority in agrotourism. This led to the selection of 12 people in the Department of Agriculture and the Ministry of Tourism and Creative Economy, tourism operators consisting of the Hotel and Restaurant Association (PHRI), the AssociationÂ of The Indonesian Tours andÂ Travel Agencies (ASITA), and farmers/agritourism partners. Upon the analysis using the Analytic Hierarchy Process (AHP), the results showed that authentic experience should be prioritized with agrotourism actors or partners playing a big role in the marketing process. Furthermore, the addition of attractions with actors or partners is expected to play a key role in offering authentic experiences to tourists as a prioritized alternative strategy. These findings, therefore, showed the need for coordination and collaboration, intensifying marketing communications as well as the provision of tour packages to increase agrotourism marketing in the study area.